ORGANIZATIONAL AND LEGAL PRINCIPLES OF METHODS OF EVALUATING THE PERFORMANCE OF THE HEAD OF THE AVIATION ENTERPRISE - Bezzubov, Dmytro; Starodubova, Olga (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of the article is to consider the issue of the legal bases of the methods of evaluating the activity of the head of the aviation enterprise, the definition of criteria for evaluating the results of the activity of the head of the aviation enterprise, the formation of adequate mechanisms for increasing the level of economic sustainability of the aviation enterprise. Research methods: the main scientific methods of system analysis, formal logic and the method of classifications were used during the work. The method of system analysis is applied accordingly to determine general approaches to the evaluation of the activity of the head of the enterprise. The method of formal logic made it possible to determine scientific views on the categories of economic activity of aviation enterprises and to evaluate the results of the activities of the head of the aviation enterprise. The method of classifications made it possible to determine the ways of further improvement of the institutional foundations of ensuring the activities of aviation enterprises. Results: the study of the issue of the legal foundations of the methods of evaluating the performance of the head of an aviation enterprise is part of the study of the problems of economic and aviation law. Improving the procedures for evaluating the performance of the head of the aviation enterprise will make it possible to increase the efficiency of the development of the aviation enterprise. The results of the research presented in this scientific article make it possible to determine further steps in the study of organizational and legal problems of evaluating the performance of aviation enterprise managers. Discussion: problems of evaluation methods of aviation enterprise managers are applied from the point of view of the development of economic and aviation law.